Spiritual health in women with multiple sclerosis and its association with self-esteem - Vahid Shaygannejad; Shahla Mohamadirizi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Spiritual health is one of the four dimensions of health in humans, and the others are physical, psychological, and social dimensions. This dimension is essential to increase the adaptation to the disease. Therefore, this study was aimed to determine spiritual health in women with multiple sclerosis (MS) and its association with self-esteem. METHODS: This is a descriptive cross-sectional study, and 210 women with MS referring to Ayatollah Kashani Hospital affiliated to Isfahan University of Medical Sciences were selected using convenience sampling method. The data were collected by questionnaires of demographic characteristic questionnaire (6 items), Rosenberg Self-esteem Scale (10 items), and Ellison and Paloutzian Spiritual Well-being Questionnaire (20 items). Data were analyzed using descriptive statistics, Pearson's correlation coefficient, and multiple regression analysis at a significance level of 0.05. RESULTS: The mean and standard deviation of spiritual health (including religious health and existential health) and self-esteem in MS patients were 48.8 ± 6.80, 44.7 ± 6.70, and 3.21 ± 2.5, respectively. The results showed that 95.2% of the research units had moderate-to-high spiritual (religious and existential) health and 57.7% had high self-esteem. Pearson's correlation coefficient also showed a significant positive correlation between religious health and existential with self-esteem (r = 0.22, P = 0.03 and r = 0.24, P = 0.01, respectively). CONCLUSIONS: In this study, most of the women with MS had high levels of spiritual health and self-esteem. This can be used as a coping strategy and has a protective effect against stress-induced illness and even against complications of the treatment. In addition, in some cases, it is effective in alleviating frustration in these patients.